2014
DOI: 10.1159/000363027
|View full text |Cite
|
Sign up to set email alerts
|

Dipalmitoleoylphosphoethanolamine as a PP2A Enhancer Obstructs Insulin Signaling by Promoting Ser/Thr Dephosphorylation of Akt

Abstract: Background/Aims: The phospholipid phosphatidylethanolamine is implicated in the regulation of a variety of cellular processes. The present study investigated the effect of phosphatidylethanolamines such as 1,2-diarachidonoyl-sn-glycero-3-phosphoethanolamine (DAPE), 1,2-dilinoleoyl-sn-glycero-3-phosphoethanolamine (DLPE), 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), and 1,2-dipalmitoleoyl-sn-glycero-3-phosphoethanolamine (DPPE) on protein phosphatases, Akt1/2 activity, GLUT4 mobilizations, and glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In our earlier study, 1,2-dipalmitoleoyl-sn-glycero-3-phosphoethanolamine (DPPE), which contains palmitoleic acid on the α and β position, induced apoptosis of malignant pleural mesothelioma (MPM) cells by enhancing activities of protein phosphatase 2A (PP2A) and protein tyrosine phosphatase 1B (PTP1B) [12]. Another phosphatidylethanolamine 1,2-dilinoleoyl-sn-glycero-3-phosphoethanolamine (DLPE), which contains linoleic acid on the α and β position, also enhanced PP2A and PTP1B activities, but such effect was not obtained with 1,2-diarachidonoylsn-glycero-3-phosphoethanolamine (DAPE), which contains arachidonic acid on the α and β position, or 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), which contains oleic acid on the α and β position [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier study, 1,2-dipalmitoleoyl-sn-glycero-3-phosphoethanolamine (DPPE), which contains palmitoleic acid on the α and β position, induced apoptosis of malignant pleural mesothelioma (MPM) cells by enhancing activities of protein phosphatase 2A (PP2A) and protein tyrosine phosphatase 1B (PTP1B) [12]. Another phosphatidylethanolamine 1,2-dilinoleoyl-sn-glycero-3-phosphoethanolamine (DLPE), which contains linoleic acid on the α and β position, also enhanced PP2A and PTP1B activities, but such effect was not obtained with 1,2-diarachidonoylsn-glycero-3-phosphoethanolamine (DAPE), which contains arachidonic acid on the α and β position, or 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), which contains oleic acid on the α and β position [13].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose uptake assay was carried out by the method as described previously 1 13 14 . Differentiated 3T3-L1-GLUT4myc adipocytes without and with IR knock-down were incubated in a Krebs-Ringer-HEPES buffer containing 0.2% (w/v) BSA supplemented with 10 mM glucose at 37 °C for 1 h. Then, cells were not treated and treated with diDCP-LA-PE or insulin in phosphate-buffered saline supplemented with 10 mM glucose at 37 °C for 2 h. After treatment, extracellular solution was collected and glucose was labeled with p -aminobenzoic ethyl ester (ABEE), followed by HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…PE is shown to regulate membrane fusion, cell cycle, autophagy, apoptosis, cognitive function, and glucose homeostasis [5-10]. We have earlier found that the PE derivative 1, 2- O -bis-[8-{2-(2-pentyl-cyclopropylmethyl)-cyclopropyl}-octanoyl]- sn - glycero-3-phosphatidylethanolamine (diDCP-LA-PE) is capable of mimicking intracellular insulin signaling [11].…”
Section: Introductionmentioning
confidence: 99%